The effect of diabetes mellitus on rat skeletal extensor digitorum longus muscle tissue: An FTIR study. Issue 3 (2007) - Bozkurt Bozkurt, Ozlem Ozlem; Bilgin Bilgin, Mehmet Dincer Mehmet Dincer; Severcan Severcan, Feride Feride
Abstract : Diabetes mellitus (DM) is a chronic disorder of carbohydrate, fat and protein metabolism, which is characterized by a defective insulin secretory response. Skeletal muscle takes role in determination of carbohydrate and lipid metabolism, therefore; it is one of the target tissues of diabetes. Herein this study, application of Fourier Transform Infrared (FTIR) spectroscopy in diabetic skeletal Extensor Digitorum Longus (EDL) muscle tissues will be presented which highlight the promise of this technique in medical research. Type I DM was induced in rats by injection of streptozotocin (STZ) which is one of the most popular experimental models. In diabetes, a significant increase was observed in lipid order together with an increase in hydration of phospholipid molecules in membrane structure. There was a decrease in lipid and nucleic acid content in diabetic EDL muscles. A dramatic increase in the bandwidth of amide II band (1540 cm −1 ) and shifting of the position of this band to lower frequency values in diabetes was observed indicating structural changes occurring in proteins of diabetic EDL muscles.